EFISIENSI PENGGUNAAN INPUT USAHATANI BAWANG PUTIH LOKAL EBANDI MIOMAFFO BARAT KABUPATEN TIMOR TENGAH UTARA - Simon Juan Kune; Adeline Norawati Hutapea (JURNAL MANAJEMEN AGRIBISNIS, 2019)
Abstract The purpose of this research is to know the description of farming system and to analyze the technical and allocative efficiency of Eban local garlic farming by using survey method while the data used are primary and secondary data. Data analysis using descriptive analysis and stockhastic frontier analysis. The results of the general overview of Eban's local garlic farms include; land preparation, seed preparation, planting, maintenance and harvesting. While technically Eban local garlic farming is efficient where the analysis conducted for 50 respondents shows the efficient average achieved by 92% while the allocation of local garlic farming has not been efficient because of the calculation of NPMx / px > 1.